Hubungan Bauran Pemasaran Pie Susu dengan Keputusan Pembelian Wisatawan Domestik di Kota Denpasar - SARAH IMANUELLA TAMBUNAN; KETUT BUDI SUSRUSA; IGAA LIES ANGGRENI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2019)
Correlation of Milk Pie Marketing Mix on Domestic Tourist Buying Decisions in Denpasar City The purpose of this study was to determine whether the marketing mix which includesproduct, price, place, and promotion factors have correlation with the buying decisions ofdomestic tourists in buying milk pies and to find out the most dominant variablesconsidered by domestic tourists in buying milk pies in the of City Denpasar. Productvariables (X1), prices (X2), place (X3), and promotions (X) are the independent variablesin this study, with the dependent variable namely the buying decision of domestic tourists(Y). The type of research data used is quantitative and qualitative data. Data sources wereobtained from the results of interviews and observations in the companies of Pie SusuAsli Enaaak and Pie Susu Special, and by using literature studies of books, notes relatingto research and the internet. Data analysis used was the analysis of Rank Spearmancorrelation using SPSS 23. The marketing mix which includes products, prices, place, and promotions, has a positiveinfluence on the buying decisions of domestic tourists in Denpasar City. Milk pieproducts are variables that have a dominant influence on purchasing decisions ofdomestic tourists in Denpasar City. Based on the results of Rank Spearman's correlationanalysis, it is suggested to the milk pie companies to pay attention to the distributionchannel variables as well as to establish cooperation in the future with Balinese gift shops 4and courier services. It is also hoped that they improve the promotion variables byutilizing social media to promote milk pie products, and maintain the gift offer to attractdomestic tourists.